Features of chemical changes in fuels at storage - Матвєєва, О.Л.; Столінець, С.Л. (Proceedings of National Aviation University (archive), 2004)
The analysis and theoretical substantiation of scientific researches on features of chemical changes in fuels is lead. Working mechanisms of oxidation which occur in hydrocarbonic fuels are systematized.